Quality and frequency of antenatal care and the incidence of stunting in Indonesia: an analysis of IFLS 5 - Dewi, Zidna Akmala; Hakimi, Mohammad; Kandarina, BJ. Istiti (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to analyze the relationship between the quality of antenatal care and the frequency of antenatal care, as well as its impact on stunting in Indonesia, as reported in the 2014 IFLS 5 data. Methods: This study employed an observational analytic design using secondary data from the Indonesian Family Life Survey (IFLS) 5, with a historical cohort study approach. The population in this study consisted of all children aged 6-23 months who were domiciled in 13 provinces, which were the subject of IFLS 5 data. The analysis was conducted using the chi-squared test and logistic regression. Results: The results of the bivariate analysis showed that there was no significant relationship between the quality of antenatal care for the incidence of stunting, with the p-value=0.52 (RR=1.09; CI 95% = 0.83–1.41) but the frequency of antenatal care had a significant relationship with incidence of stunting with the p-value=0.01 (RR=1.52; CI 95% = 1.11–2.08). The results of multivariate analysis of the frequency of antenatal care influenced the incidence of stunting by considering the variables of blood pressure measurement, maternal work, and iron supplements with a p-value <0.01 (OR=2.015; 95% CI = 1.18–3.44). Conclusion: This study found that the frequency of antenatal care is significantly associated with the incidence of stunting.